Steppe Eagle in the Kharkiv Region From Ukraine: Registration, Possible Causes of the Observed Phenomena - Stanislav G. Viter (Пернатые хищники и их охрана, 2017)
The Steppe Eagle (Aquila nipalensis) is a very rare vagrant in Ukraine. It bred here in 1970s, and adults were recorded in summer on their nesting sites up until 1981. In the Kharkiv region (Eastern and N–E. Ukraine) the species was noted as breeding in the second half of 19 century. Our survey was carried out in 2003–2016. For this period, we have known about the 5 registrations of Steppe Eagles in 5 districts. Two of these registrations were made at the breeding season (second half of May – mid-July), one – at the period of post-nesting movements (the second half of July - the first half of August) and 2 – at the period of migration (March – middle of May, middle August – October).